(untitled) (Nordic Journal of African Studies, 2008)
The validity of two famine theories at the political level is assessed using the Malawi 2002 famine: (i) Amartya Sen’s thesis of a positive impact of democracy on famine protection and (ii) De Waal’s thesis stressing the importance of anti-famine contracts. Both theses fall short of explaining the Malawi 2002 famine, as it occurred despite the existence of pluralistic institutions, a free press, and strong government attention to issues of food security. Rather, the famine appears to be caused by deteriorating donor relations just as the weak Malawi government was particularly dependent on international humanitarian aid.